Correction to “A Career in Catalysis: Daniel Resasco” - Resasco, Joaquin; Albanese, Jimmy Faria; Alvarez, Walter; Crossley, Steven; Haller, Gary L.; Herrera, José E.; Jacobs, Gary; Lercher, Johannes; Li, Gengnan; Lobban, Lance; Noronha, Fábio Bellot; Ruiz, M. Pilar; et al. (My University, 2026)
In the original manuscript, José E. Herrera was inadvertently omitted from the author list. He contributed to the section on carbon nanotubes. The author list has been corrected to reflect his contribution.